An Enzyme‐Mediated Amplification Strategy Enables Detection of β‐Lactamase Activity Directly in Unprocessed Clinical Samples for Phenotypic Detection of β‐Lactam Resistance. (26th September 2018) - deBoer, Tara R.; Tarlton, Nicole J.; Yamaji, Reina; Adams‐Sapper, Sheila; Wu, Tiffany Z.; Maity, Santanu; Vesgesna, Giri K.; Sadlowski, Corinne M.; DePaola, Peter; Riley, Lee W.; Murthy, Niren
Abstract: Biochemical assays that can identify β‐lactamase activity directly from patient samples have the potential to significantly improve the treatment of bacterial infections. However, current β‐lactamase probes do not have the sensitivity needed to measure β‐lactam resistance directly from patient samples. Here, we report the development of an instrument‐free signal amplification technology, DETECT, that connects the activity of two enzymes in series to effectively amplify the activity of β‐lactamase 40 000‐fold, compared to the standard β‐lactamase probe nitrocefin. Abstract : Strength in numbers : A dual‐enzyme trigger‐enabled cascade technology (DETECT) affords a 40 000‐fold signal amplification of β‐lactamase activity. This instrument‐free amplification approach enabled the detection of β‐lactamase activity directly from unprocessed clinical urine samples, as a marker of β‐lactam resistance in Gram‐negative bacteria causing urinary tract infections.